Comparison of Prognostic Performance between Fisher and Modified Fisher Scales for Patients with Aneurysmal Subarachnoid Hemorrhage - Rabello, Pedro Henrique Mouty; Rabelo, Nicollas Nunes; Telles, João Paulo Mota; Coelho, Antônio Carlos Samaia da Silva; Yoshikawa, Marcia Harumy; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Objective The present study aims to assess and compare the prognostic value of these two scales for predicting mortality.Method We reviewed 172 patients with aneurysmal subarachnoid hemorrhage, who were followed-up for 6 months. The Fisher and modified Fisher scales were evaluated for the prediction of mortality using logistic regressions.Results The Fisher scale was associated with mortality (odds ratio [OR]: 2; 95% confidence interval [CI]: 1.09–4.05) in the multivariate analysis. The modified Fisher scale was not associated with mortality in the multivariate analysis (OR: 1.39; 95% CI: 0.9–2.29), nor in the univariate analysis (OR: 1.24; 95%CI: 0.87–1.86). There was no significant association between Fisher score and unfavorable functional outcomes (mRS > 2) in the univariate analysis (OR: 1.33; 95%CI: 0.92–1.92), nor in the multivariate analysis (OR: 1.37; 95%CI: 0.92–2.05). There was no significant association between modified Fisher scores and unfavorable functional outcomes in the univariate analysis (OR: 1.16; 95%CI: 0.88–1.52). There was also no significant association in the multivariate analysis (OR: 1.18; 95%CI: 0.88–1.57).Conclusion Only the Fisher scale was associated with mortality. Neither of the two scales was associated with unfavorable functional outcomes (mRS > 2).
Keywords: fisher; modified fisher; subarachnoid hemorrhage; intracranial aneurysm; prognosis